2014
DOI: 10.4049/jimmunol.1302492
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Antigen Scavenging, Cross-Presentation, and CD8+ T Cell Priming: A New Role for Lymphatic Endothelial Cells

Abstract: Until recently, the known roles of lymphatic endothelial cells (LECs) in immune modulation were limited to directing immune cell trafficking and passively transporting peripheral Ags to lymph nodes. Recent studies demonstrated that LECs can directly suppress dendritic cell maturation and present peripheral tissue and tumor Ags for autoreactive T cell deletion. We asked whether LECs play a constitutive role in T cell deletion under homeostatic conditions. In this study, we demonstrate that murine LECs under non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(202 citation statements)
references
References 63 publications
8
189
0
Order By: Relevance
“…24 Furthermore, tumor-associated LECs may directly cross-present tumor antigens to CD8 + T cells and render them dysfunctional in the tumor microenvironment. 25 , 26 LECs can also inhibit the maturation of dendritic cells, 27 secrete inhibitory molecules such as indoleamine 2,3-dioxygénase (IDO), inducible nitric oxide synthase (iNOS) and transforming growth factor beta (TGF-β), and impair T cell activation through expression of inhibitory receptor ligands (e.g. programmed cell death ligand 1 and 2 (PD-L1 and 2)).…”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, tumor-associated LECs may directly cross-present tumor antigens to CD8 + T cells and render them dysfunctional in the tumor microenvironment. 25 , 26 LECs can also inhibit the maturation of dendritic cells, 27 secrete inhibitory molecules such as indoleamine 2,3-dioxygénase (IDO), inducible nitric oxide synthase (iNOS) and transforming growth factor beta (TGF-β), and impair T cell activation through expression of inhibitory receptor ligands (e.g. programmed cell death ligand 1 and 2 (PD-L1 and 2)).…”
Section: Introductionmentioning
confidence: 99%
“…Large or opsonized antigens are taken up by subcapsular macrophages, whereas smaller antigens flow into small conduits lined with follicular DCs in which they can be taken up directly by antigen-specific B cells (21). On the other hand, LECs have access to all lymph-borne antigens, and it was recently shown that LECs can actively scavenge these antigens, process them intracellularly, and cross-present them to T cells for deletional tolerance (22,23), which is discussed in more detail later. Furthermore, LECs can retain antigen for long periods of time and may play a role in recalling memory T cells (24).…”
Section: Lymph Flow Of Antigensmentioning
confidence: 99%
“…Second, LECs (as well as FRCs) constitutively express and present self-antigen on MHC class I molecules to delete autoreactive T cells and thus help maintain peripheral tolerance to these self-antigens (37,38). Third, as mentioned above, it is now known that LECs can actively scavenge exogenous lymph-borne antigens and process them for cross-presentation on MHC class I molecules (22,23). Because LECs lack costimulatory molecules necessary to activate effector CD8 T cells, and instead they express high levels of the inhibitory ligand PD-L1 (39), LEC presentation of the peptide-MHC class I complex can drive deletional tolerance of na€ ve CD8 T cells (22,23).…”
Section: Lymphatic Endothelial Cells Modulate Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-draining LNs contain both tumor antigen-primed T cells with up-regulated checkpoint molecules and immune cells with up-regulated checkpoint ligands (36). LN-resident DCs can induce tolerance in CD8 + T cells, and LN stromal cells can play similar roles (77)(78)(79)(80). These factors suggest that the tumor-draining LN may contain important biomarkers relevant to diagnosis.…”
Section: Tumor Characterizationmentioning
confidence: 99%